THE CRISIS OF THE LEFT IN THE CZECH REPUBLIC, A PARTY-ELITE PERSPECTIVE (KSČM AND SOCDEM) (Studia Politica. Romanian Political Science Review, 2025)
For approximately two decades, the Czech Republic has stood out as an outlier in Central and Eastern Europe (CEE), being the only country where a largely unreformed communist successor party, the Communist Party of Bohemia and Moravia (KSČM), hasconsistently enjoyed stable and significant electoral support. Simultaneously, a robust social-democratic left with no direct ties to the former communist party played a major role in Czech politics. The Czech Social Democratic Party (ČSSD), originally founded in 1878,having been the largest or second-largest party in the country for over a decade. However, in the broader European context of left-wing decline and the rise of anti-establishment populist challengers, both parties have experienced sharp electoral downturns. In the 2021 elections, KSČM lost its parliamentary representation, a fate shared by ČSSD, now renamed Sociální Demokracie (SOCDEM), which faces an even deeper crisis. These setbacks occurred alongside the rise of new populist forces such as ANO and Freedom and Direct Democracy (SPD), which have drawn support from traditional centre-left constituencies. Despite these challenges, both parties remain politically active, with KSČM experiencing a modest revival under a more nationalist-conservative orientation. In light of this context, this paper has two primary aims. First, it traces the electoral decline of KSČM and SOCDEM over the past decade by analyzing election results and party positioning. Second, it explores how party elites interpret the crisis and identify potential sources of resilience. Methodologically, the study combines quantitative data with qualitative interviews and party document analysis. Overall, it contributes to understanding the crisis and transformation of the Czech left within the recent political landscape, as well as its implications for the broader crisis of the left in Eastern Europe.
Keywords: party politics; social democracy; radical left; Eastern Europe; elites